Enterprise Architecture Planning in Hydroponic Cultivation Business Units Using TOGAF ADM - Ari Lathifah; Muhamad Irsyad; Nur Ihsan Fajar Ramadhan; Nurul Islah Watajdid; Fitroh (School of Industrial and System Engineering, Telkom University, 2022)
Businesses in the field of hydroponics also require better management of information systems in the digitalera so they can take advantage of regular supply, targeted marketing, and gain new customers. Informationsystems are made into a necessity in the management of organizations or companies to facilitate the entireproduction, distribution and management of the company. Puji Hydroponics is a business unit in TangerangRegency that is engaged in agriculture, especially in producing vegetables using hydroponic techniques. Theproblem faced by Puji Hydroponics is that until now Puji Hydroponics does not have a formal planningstrategy. The formulation and management of strategies is ad hoc to the extent of certain needs andconditions. The impact that arises if there is no strategic planning of information systems or a maturecorporate architecture is the lack of services provided to customers. This study aims to make a corporatearchitectural plan for the hydroponic cultivation business unit at Puji Hydroponics using TOGAF ADM. Theresults of this study are business blueprint planning, application architecture, architectural data, architecturaltechnology that can be a reference for other hydroponic cultivation business units in planning enterprisearchitecture for optimization and business growth in the long term.